2018
DOI: 10.1016/j.dib.2018.04.136
|View full text |Cite|
|
Sign up to set email alerts
|

Data on insulin therapy refusal among type II diabetes mellitus patients in Mashhad, Iran

Abstract: Insulin has been considered as a therapy option of last resort in type 2 diabetes (T2DM) management. Delay in insulin therapy is common in these patients. This study collected the data on the factors associated with insulin refusal in poorly controlled T2DM patients prior to insulin therapy. The data collected from two endocrinology outpatient clinics affiliated by Islamic Azad University of Mashhad, Iran (IAUM) from January 2016 to September 2017. Study population was adults with non-insulin-using type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The fear of insulin injection and puncturing for glucose measurement leads to a problem in starting diabetes treatment [30][31][32][33][34]. In the study of Rubin et al [35] investigating the problems in insulin treatment, 20% of the patients were found to experience anxiety due to injection, 37% were found to have injectionrelated pain.…”
Section: Discussionmentioning
confidence: 99%
“…The fear of insulin injection and puncturing for glucose measurement leads to a problem in starting diabetes treatment [30][31][32][33][34]. In the study of Rubin et al [35] investigating the problems in insulin treatment, 20% of the patients were found to experience anxiety due to injection, 37% were found to have injectionrelated pain.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored potential factors associated with insulin refusal in patients with diabetes prior to insulin therapy 11,14–16. Mostafavian et al11 showed lower rates of adherence among females, patients with lower educational level, single patients, and patients with more than 1 year of diabetes duration . Similarly, our findings revealed that education level had a significant association with willingness to use insulin.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main barriers against initiating insulin therapy is psychological insulin resistance among patients 10. In Mostafavian et al's study,11 the most prevalent challenges against insulin therapy in poorly controlled T2DM patients were the pain of insulin injection (78.2%) and fear of injecting oneself with a needle (74.5%) . Mirahmadizadeh et al12 revealed that the patients’ main concerns about insulin therapy were insurance coverage, illiteracy, nondiabetic regimens, misconceptions about insulin therapy, and fear of insulin injection…”
Section: Introductionmentioning
confidence: 99%
“…When the scale is scored, positive items are scored in reverse. The sum of the four positively expressed items (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) provides the positive evaluation sub-dimension while the sum of 16 negatively expressed items (16-80) provides the negative evaluation sub-dimension. Total scale score is obtained by adding the 16 items with negative expressions and the four items with positive expressions after they are reversed.…”
Section: Data Collectionmentioning
confidence: 99%
“…[12,13] Patients may be resistant to insulin use due to reasons such as pain, hypoglycemia, accelerated weight gain, feelings of inadequacy and ineffectiveness in individuals as a result of decreased independence, and feelings of embarrassment in the community related to using insülin. [14][15][16] The sooner diabetes management training is initiated, the lower will be the rate of complications and associated mortality. It has been observed that diabetic patients spend their lives more comfortably, acquire self-efficacy and enjoy a higher quality of life with successful symptom management.…”
Section: Introductionmentioning
confidence: 99%